Wheeze among Pneumonia Patients in Paediatrics Department of Patan Hospital - Shrestha, Sita Ram; Yadhav, B; Shresta, S (Journal of Nepal Paediatric Society, 2011)
Background: Acute respiratory infections are major causes of morbidity and mortality in children in developing countries. It is estimated that 3.9 million children die annually from acute respiratary diseases and most of them in developing countries. In significant cases, wheeze is associated with Pneumonia. This study was done to find out the outcome of pneumonia patients admitted in the paediatric ward with wheeze and without wheeze in terms of hospital stay, age predominance, sex ratio, mortality and morbity of patients. Some comorbidies of patients were also studied, Methods: This was a retrospective study done in the paediatric ward of Patan Hospital from April-June 2004 to March-April 2006 AD with following inclusion and exclusion criteria. All the children presented to Emergency ward up to 14 years with symptoms and sign of pneumonia were included in the study(high grade fever with chills and rigor,cough,fast breathing,creps and wheeze in auscultation)Age more than 14 years,history of Asthma,Tuberculosis,Acute wheeze associated with cardiac problems were excluded from study.Pneumonia patients admitted not from Emergency department were also excluded from study. Pneumonia with wheeze, outcome, and the hospital stay were studied. The outcome was measured in terms of improvement, deterioration or death of patients. Co morbidities associated with Pneumonia were also studied. Results: Out of 4620 children admitted in pediatric ward eleven hundred and sixty four (Twenty five percent) cases were of pneumonia and among them two hundred eighty three(twenty four percent) had wheeze. Majority of patients with pneumonia having wheeze falls on age group in between 2 and 12 months, followed by 1-5 years. The male children were more frequently affected. The co morbidities were febrile seizure, acute gastroenteritis, sepsis and urinary tract infection. Conclusion: The children admitted in Paediatric ward with Pneumonia were eleven hundred and sixty four and with wheeze were two hundred and eight three. Among them male were more than females. Majority of patients falls on age group two to twelve months. and study showed that they had prolonged hospital stay in relation to without wheeze. Three percent of the cases had blood culture positive among eleven hundred and sixty four sample Key words: Acute respiratory infections (ARI); Wheeze; Paediatric ward; Sepsis; hospital stay. DOI: 10.3126/jnps.v31i2.4642 J Nep Paedtr Soc 2010;31(2):116-120